The effect of phenolic compound from Albizzia Seed on Biology of lesser grainborrer RhiZopertha dominica (coleoptera:Bostrichidae) (Baghdad Science Journal, 2004)
The lesser grain boner Rhizopertha dominica is an important insect on grain in Iraq . in this study phenol and coumarin were isolated from Albizzia lebbek . the addition of there compounds to artificial diet at concentration of 3.4,5% couse high effects on the development of the studed insect larva.the larva were unable to complete its development to adult stage. More over, using 5% coumarin larva were died.Seed germination was not affected when seed were sprayed with concentration of 3,4,5% of coumarin and phenol.